An epistemology of patient safety research: a framework for study design and interpretation. Part 3. End points and measurement. Issue 3 (2nd June 2008) - Brown, C; Hofer, T; Johal, A; Thomson, R; Nicholl, J; Franklin, B D; Lilford, R J
Abstract : This article builds on the previous two articles in this series, which focused on an evaluation framework and study designs for patient safety research. The current article focuses on what to measure as evidence of safety and how these measurements can be undertaken. It considers four different end points, highlighting their methodological advantages and disadvantages: patient outcomes, fidelity, intervening variables and clinical error. The choice of end point depends on the nature of the intervention being evaluated and the patient safety problem it has been designed to address. This paper also discusses the different methods of measuring error, reviewing best practice and paying particular attention to case note review. Two key issues with any method of data collection are ensuring construct validity and reliability. Since no end point or method of data collection is infallible, the present authors advocate the use of multiple end points and methods where feasible.